Tradition : a feeling for the literary past - Lerer, Seth, 1955- (Literary agenda., 2016)
Seth Lerer explores our relationship to the literary past in an age marked by historical self-consciousness, critical distance, and shifts in cultural literacy. He examines a range of fiction, poetry, and criticism in order to understand the ways in which the literary past makes us, and how we create canons for reading, teaching, and scholarship.